2000
DOI: 10.2134/jeq2000.00472425002900030025x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Changes in the Extractability and Bioavailability of Zinc and Cadmium after Sludge Application

Abstract: Changes in the extractability and uptake by crops of sludge metals in a long‐term field experiment, started in 1942, were measured to assess whether Zn and Cd are either fixed by the sludge/soil constituents or are released as the sludge organic matter (OM) decomposes. Total and 0.1 M CaCl2‐extractable concentrations of Zn and Cd in soil and total concentrations in crops were measured on archived crop and soil samples. Extractability of Zn as a proportion of the total ranged from 0.5 to 3% and that of Cd from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 0 publications
4
60
0
2
Order By: Relevance
“…Also, sewage sludge used in this study compared to desert soil was found to have higher levels of N, P, and K than in desert soil, hence, the contents of these elements gradually increased as the ratio of sewage sludge increased in sewage sludge desert soil mixtures. The main problems of an excessive application of sewage sludge are plant toxicity due to the accumulation of heavy metals in soils (McGrath et al, 2000) but also the increase in its salt content (Hao and Chang, 2003). Sewage sludge metal contents could be arranged in the following order according to their contents; Zn > Cu > Pb > Cd.…”
Section: Soil Analysismentioning
confidence: 99%
“…Also, sewage sludge used in this study compared to desert soil was found to have higher levels of N, P, and K than in desert soil, hence, the contents of these elements gradually increased as the ratio of sewage sludge increased in sewage sludge desert soil mixtures. The main problems of an excessive application of sewage sludge are plant toxicity due to the accumulation of heavy metals in soils (McGrath et al, 2000) but also the increase in its salt content (Hao and Chang, 2003). Sewage sludge metal contents could be arranged in the following order according to their contents; Zn > Cu > Pb > Cd.…”
Section: Soil Analysismentioning
confidence: 99%
“…How much do the chemical forms in which these metals occur -and their carrier phases -change over time, when comparing newly spread sludge with 5-to 10 year-old residues (McGrath et al, 2000;Bergkvist et al, 2003)? Which constituents of the receiving soils, such as iron and manganese oxides, clay minerals and organic matter, will immobilise such metals?…”
Section: Introductionmentioning
confidence: 99%
“…Some authors also reported similar findings (Jordao et al, 2003;Karami et al, 2009 andMcGrath et al, 2000). One aspect which should be taken into account is that the addition of sludge not only results in an increase in the total concentrations of metals, but also in the quantity of organic matter, which may have a direct effect on their solubility and bioavailability (McBride et al, 1997).…”
Section: Discussionmentioning
confidence: 81%